Jane Williams (Ysgafell) - Roberts, Gwyneth Tyson (University of Wales Press, 2020)
The first full account of the life and work of a nineteenth-century woman who carved out a unique career as an important writer in English on Welsh subjects.
Keywords: Williams, Jane, -- 1806-1885.; Historians -- Wales -- Biography.; BIOGRAPHY & AUTOBIOGRAPHY / Literary Figures; Historians; Wales; Biographies